Real Time Conference Gateway For Heterogeneous Clients : Real Time Switching Clients And Inter-Asterisk Exchange Clients - Kolhar, Manjur Sayyad Badasha (2010)
Various standards organizations have considered signaling for voice and video over Internet Protocol(IP) from different approaches. The Inter-Asterisk eXchange (IAX) protocol is used as the promising VoIP protocol by the service provider because of its simplicity and NAT friendliness. Meanwhile, the Real time SWitching (RSW) has the ability to combine voice and video services. Incidentally, these two heterogeneous clients pose considerable problems for users who have to choose between two solutions offering different advantages and disadvantages. While RSW is being used in many areas, IAX is being deployed in many VoIP services. Hence, RSW interoperability and coexistence with IAX is considered very important to support new deployments that could use RSW as an alternative packet telephony signaling protocol. We proposed and implemented the conference gateway (CG), which enables the heterogeneous clients to communicate seamlessly. It has two modules, one is signaling, the other is media module. In signaling module, we have converted signaling and control messages of RSW and IAX respectively to achieve seamless signaling communication between heterogeneous clients via CG. The signaling module includes authentication of heterogeneous clients (RSW and IAX) before they start communication, conversion of Uniform Resource Indicator to reach remote clients, setup media calls and exchange media capability.